2021
DOI: 10.3389/fphar.2021.717932
|View full text |Cite
|
Sign up to set email alerts
|

Experience of a Strategy Including CYP2C19 Preemptive Genotyping Followed by Therapeutic Drug Monitoring of Voriconazole in Patients Undergoing Allogenic Hematopoietic Stem Cell Transplantation

Abstract: Many factors have been described to contribute to voriconazole (VCZ) interpatient variability in plasma concentrations, especially CYP2C19 genetic variability. In 2014, Hicks et al. presented data describing the correlation between VCZ plasma concentrations and CYP2C19 diplotypes in immunocompromised pediatric patients and utilized pharmacokinetic modeling to extrapolate a more suitable VCZ dose for each CYP2C19 diplotype. In 2017, in our hospital, a clinical protocol was developed for individualization of VCZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Therefore, analysis of the CYP2C19 genotype may assist in clinical practice and improve patient outcomes. And it says the similar as García-García proved in 2021 (32).…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, analysis of the CYP2C19 genotype may assist in clinical practice and improve patient outcomes. And it says the similar as García-García proved in 2021 (32).…”
Section: Discussionmentioning
confidence: 55%
“…Subtherapeutic concentrations were prevented in 83.8% of CYP2C19 rapid metabolizers receiving interventional dosing versus 46.2% receiving standard dosing [10]. One year later, Garcia-Garcia et al (2021) [11] reported analyses of 28 immunocompromised pediatric patients in whom preemptive CYP2C19 genotyping and therapeutic VCZ monitoring was performed. The final objective was to compare its results with the results obtained by Hicks et al and [12] used a PK model to optimize the voriconazole dosing regimen in children with severe disease.…”
Section: Voriconazole and Cyp2c19 Metabolizer Statusmentioning
confidence: 99%
“…PGx‐guided therapy could guide the use of medications most likely to be effective, thereby reducing unnecessary medical complications and financial strain, as well as improve QoL. The use of PGx‐guided supportive care has been reported with opioids to help mitigate cancer‐related pain, prophylactic use of voriconazole in intermediate to high infection risk hematological malignancies, and ondansetron for chemotherapy‐induced nausea and vomiting (CINV) 19–25 . Institutions are increasingly implementing panel‐based PGx tests to preemptively guide medications with CPIC guidelines 26–28 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of PGx‐guided supportive care has been reported with opioids to help mitigate cancer‐related pain, prophylactic use of voriconazole in intermediate to high infection risk hematological malignancies, and ondansetron for chemotherapy‐induced nausea and vomiting (CINV). 19 , 20 , 21 , 22 , 23 , 24 , 25 Institutions are increasingly implementing panel‐based PGx tests to preemptively guide medications with CPIC guidelines. 26 , 27 , 28 However, utilization of a panel‐based PGx approach to specifically guide supportive care medications in patients with cancer has not been widely described.…”
Section: Introductionmentioning
confidence: 99%